2010
DOI: 10.1002/fld.2502
|View full text |Cite
|
Sign up to set email alerts
|

An improved progressive preconditioning method for steady non‐cavitating and sheet‐cavitating flows

Abstract: SUMMARYAn improved progressive preconditioning method for analyzing steady inviscid and laminar flows around fully wetted and sheet-cavitating hydrofoils is presented. The preconditioning matrix is adapted automatically from the pressure and/or velocity flow-field by a power-law relation. The cavitating calculations are based on a single fluid approach. In this approach, the liquid/vapour mixture is treated as a homogeneous fluid whose density is controlled by a barotropic state law. This physical model is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 46 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…The computed surface pressure coefficient distribution by the present method is compared with that of Esfahanian et al, as shown in Figure , and the agreement between the numerical results is reasonable. The small difference between these two simulations may be due to different cavitation modeling approaches used and different numerical methods applied.…”
Section: Numerical Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The computed surface pressure coefficient distribution by the present method is compared with that of Esfahanian et al, as shown in Figure , and the agreement between the numerical results is reasonable. The small difference between these two simulations may be due to different cavitation modeling approaches used and different numerical methods applied.…”
Section: Numerical Resultssupporting
confidence: 57%
“…The small difference between these two simulations may be due to different cavitation modeling approaches used and different numerical methods applied. Esfahanian et al have used the finite volume method to solve the one‐fluid cavitation model with a barotropic state law and here the NDGM is applied to solve the multiphase transport equation–based model considering the mass transfer in the formulation.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The AC coefficient determines the stability and convergence rate of the AC scheme (Turkel, 1987;Malan et al, 2002;Esfahanian et al, 2012), and its choice is often case dependent. For example, for an inviscid and high Reynolds flow problem, Turkel(1987) showed that if b was close to the local convective velocity, the AC simulation achieved a better convergence rate ).…”
Section: Semi-lagrangian Artificial Compressibility Methodsmentioning
confidence: 99%
“…Especially, the cavitation model is a critical method determining the accuracy of numerical simulation. Esfahanian et al (2012) applied a barotropic state equation that links the density variations to the local static pressure to solve the mixture density in the cavitating flow and this method is famous as the cavitation model based on state equation. The other popular approach to simulate cavitating flows is called as the cavitation model based on transport equation, which solves an additional transport equation for either the mass or volume fraction of vapor, with appropriate source/sink term(s) to regulate the mass transfer between the liquid and vapor phases.…”
Section: Introductionmentioning
confidence: 99%